Forensic investigations of disasters: Past achievements and new directions - Irasema Alcántara-Ayala; Ian Burton; Allan Lavell; Anthony Oliver-Smith; Alonso Brenes; Thea Dickinson (Jàmbá, 2023)
In the 2020s, understanding disaster risk requires a strong and clear recognition of values and goals that influence the use of political and economic power and social authority to guide growth and development. This configuration of values, goals, power and authority may also lead to concrete drivers of risk at any one time. Building on previous disaster risk frameworks and experiences from practice, since 2010, the ‘Forensic Investigations of Disasters (FORIN)’ approach has been developed to support transdisciplinary research on the transformational pathways societies may follow to recognise and address root causes and drivers of disaster risk. This article explores and assesses the achievements and failures of the FORIN approach. It also focuses on shedding light upon key requirements for new approaches and understandings of disaster risk research. The new requirements stem not only from the uncompleted ambitions of FORIN and the forensic approach but also from dramatic and ongoing transformational changes characterised by climate change, the coronavirus disease 2019 (COVID-19) pandemic and the threat of global international confrontation, among other potential crises, both those that can be identified and those not yet identified or unknown.